Slater-Pauling-like Behavior of Spin Hall Conductivity in Pt-based Superlattices - Abdul-Muizz Pradipto; Kohji Nakamura (Journal of Mathematical and Fundamental Sciences, 2021)
The intrinsic spin Hall effect in the bulk systems of late  transition metals (Os, Ir, Pt, and Au) as well as the Pt-based superlattices were investigated by using first-principle calculations. By comparing the computed spin Hall conductivities of Pt−M superlattices (M=Os, Ir, and Au) with different compositions and those obtained from atomic bulk composition, we saw that the spin Hall conductivities (SHCs) follow the behavior described by the Slater-Pauling curve, the maximum of which is at pure Pt bulk. From the examination of the band structures of the considered systems, we found that the origin of this behavior comes from the variation of the band structures as a direct consequence of the change of the number of electrons and hybridization effects.